2016
DOI: 10.1111/ijfs.13241
|View full text |Cite
|
Sign up to set email alerts
|

Crude extract of Fuzhuan brick tea ameliorates DSS‐induced colitis in mice

Abstract: Summary Inflammatory bowel disease (IBD) is highly prevalent worldwide and includes ulcerative colitis (UC) and Crohn's disease. It is a high incidence rate disease all over the world and an inducement of colon cancer. The aim of this study was to investigate the potential protective effect of Fuzhuan brick tea (FBT) against colitis induced by dextran sulphate sodium (DSS) in mice. ICR mice were administered FBT orally for 7 days before drinking 3% DSS (w/v). The FBT significantly attenuated the symptoms of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Previous studies have shown that a dosage of 5–60 mg/kg of unaged pu-erh tea can alleviate colitis in mice better, , but the optimal dosage of aged ripe pu-erh tea has not been defined. In the previous experiment, (DSS salt, molecular weight = 36–50 kDa) DSS-treated mice, which received normal diet and 3.5% (w/v) DSS in drinking water, were given intragastric administration with various concentrations of P2006 (1, 10, 50, 100, and 200 mg/kg bw) to confirm the best concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that a dosage of 5–60 mg/kg of unaged pu-erh tea can alleviate colitis in mice better, , but the optimal dosage of aged ripe pu-erh tea has not been defined. In the previous experiment, (DSS salt, molecular weight = 36–50 kDa) DSS-treated mice, which received normal diet and 3.5% (w/v) DSS in drinking water, were given intragastric administration with various concentrations of P2006 (1, 10, 50, 100, and 200 mg/kg bw) to confirm the best concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, L. coreana , containing a characteristic phytochemical profile, showed anti‐inflammatory effects in different studies . Recently, the therapeutic effects of colitis have been found in green, black, and dark teas . However, the difference in the phytochemical composition of these teas may result in different in vitro and in vivo biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Fuzhuan brick tea (FBT), one of the unique dark teas mainly produced in the Hunan and Shanxi provinces of China with the help of aerobic or anaerobic microbial fermentation, has been used as a nutritional supplement for people in the border regions of Southern/Western China since the 1860s. , The traditional manufacturing process of FBT mainly includes withering, steaming, rolling, microbial fermentation, drying, screening, pile fermentation, compact shaping, and packaging . Nowadays, FBT has received increasing attention due to its unique flavor and various health-promoting functions, including antioxidant, hepatoprotective, antiobesity, , anti-inflammatory, and antibacterial activities. However, the bioactive components in FBT contributing to the health-promoting functions remain unclear.…”
Section: Introductionmentioning
confidence: 99%